Mechanical characterization of metal-composite laminates based on cellulosic kenaf and pineapple leaf fiber - Ng, Lin Feng; Dhar Malingam, Sivakumar; Selamat, Mohd Zulkefli; Chen, Wei Ping (Taylor and Francis Inc., 2020)
Owing to the increasing demand for high performance and lightweight materials, fiber metal laminates (FMLs) have become the alternative materials to replace metallic alloys. When the environmental friendliness of the materials is taken into consideration, plant fibers have shown an excellent potential to be employed as the reinforcements in FMLs. This work describes the mechanical behavior of kenaf and pineapple leaf fibers (PALF) reinforced metal laminates with various fiber contents, ranging from 10 wt% to 50 wt%. Fiber metal laminates were formed through the coalescence of metallic skin layers with the composite as the core. The mechanical tests were then conducted to study the tensile, flexural and Charpy impact properties of the structures. From the findings, it was concluded that both the kenaf and PALF based FMLs showed the optimum mechanical properties when the fiber content was fixed at 30 wt%. In addition, PALF based FMLs had shown higher mechanical properties over kenaf based FMLs. At a fiber content of 30 wt%, the tensile and flexural strength of PALF based FMLs were respectively 6.18% and 3.44% higher than kenaf based FMLs. In terms of impact properties, the impact strength of PALF based FMLs was 5.06% and 40.73% higher than kenaf based FMLs in the flatwise and edgewise orientations.